Determinants of Attitude Tourist in E-Tourism Usage - Wibasuri, Anggalia; Bangsawan, Satria; MS, Mahrinasari; ., Ribhan (International Journal of Engineering and Technology, 2019)
This paper examine the influence of five variables on attitude tourist: perceived ease of use, perceived usefulness, self efficacy, domain specific innovativeness, and experience. The analysis attitude tourist toward e-tourism usage gauges the moderating role of e-trust. A sample of 216 tourist of was analyzed using structural equation modeling. Result show that perceived ease of use, perceived usefulness, domain specific inovativeness, and experience significantly influence attitude tourist. E-trust moderates the impact of e-tourism usage. These results entail a better understanding of specificities, with practical actions for addressing their real needs and expectations. The study limitations, implications, along with directions for further research are discussed.Â Â Â